Indisciplina: um estudo sobre os sentidos e significados constituídos por docentes e discentes de um centro universitário particular - Leal, Wedja Maria Oliveira (2014)
This study sought to identify the senses and the meanings of indiscipline for teachers students involved in a private university located in the East Zone of São Paulo. It was analyzed the problems of indiscipline that undergraduate teachers face and how these problems are manifested and explained by the teachers and the students. It was adopted, as the theoretical framework, the Socio-Historical Psychology. Data were collected and produced by the technique known as focus groups. The materials produced through the focus groups were transcribed and analyzed aiming to construct core meaning nuclei, as proposed by Aguiar and Ozella (2013). The results suggest that the meaning of discipline for teachers and students is very similar in appearance, although having distinct origins: both groups agreed that there is not indiscipline among undergraduate students, since the mischievous conducts are viewed by most teachers as uneducated persons typical behaviors. Students, on the other hand, saw these ills-behaviors as resulting from the ignorance about the few institutional rules. It was concluded that these notions were mainly a result of the lack of clear rules able to lay the foundation of living in the university environment. It is possible to say that this research helped to show how complex the phenomenon of indiscipline in higher education is, a phenomenon that, according to the literature, is still unexplored at this level of education